Pengaruh Susut Energi (Losses) Pada Jaringan Distribusi (Studi Kasus: di PT. Krakatau Daya listrik) - Desmira Desmira (Sekolah Tinggi Teknik PLN, 2020)
PT. Krakatau Daya Listrik is a company that distributes electricity. In the distribution process of electricity distribution from generators to consumers, there is an inconsistency with the data on electrical energy supplied from power plants to the energy that is consumed. consumers are also the background of this research. The research objective is how much energy losses (losses) in the conductor that flows from the generator to the maximum and minimum consumer consumption during 2018. This research method is 1. Preparation stage by identifying problems with energy loss (Losess), 2. Pre-Research Stage This stage is looking for reference sources that will be used either from books, internet, thesis results or practical work related to the theme taken namely energy loss, 3. Data Selection Stage This stage is data collection in accordance with the targets and objectives of this study. The results of the study were the minimum losses recorded during 2018, which was (-2.041%), and the maximum value was (1.588%). The conclusion of this research is that the smaller the size of the carrier, it means that the lower the cost of distribution. And if the smaller the size that is on the conductor, it means that the voltage drop and the average total value of distribution losses per year will be even greater.